Peran Kepuasan Kerja Memediasi Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Kuta - Artana, Putu Yuwanda; SE., M.Si., Ni Wayan Mujiati (E-Jurnal Manajemen, 2022)
The aim of this study is to analyze the effect of work motivation on employee performance, the effect of work motivation on job satisfication, the effect of job satisfication on employee performance and the role of job satisfication on mediating the effect of work motivation on employee performance. This study was conducted on the employee of PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Kuta, involving 75 respondents using non probability sampling techniques. Data was collected using questionnaire based on google form, and the data was analyze using descriptive and path analysis. The result of this study are: 1) Work motivation has a positive and significant effect on employee performance, 2) Work motivation has a positive and significance effect on job satisfication, 3) Job satisfication has a positive and significance effect on employee performance, 4) Job satisfication is positively mediating the effect of work motivation on employee performance. The result of this study has implication for PT. Bank Rakyat Indonesia (Persero) Tb k Kuta regarding high work motivation, the higher the job satisfication will be, so the employee performance will increase. Keyword: work motivation, job satisfication, employee performance